SUMOylation regulates Rb hyperphosphorylation and inactivation in uveal melanoma. Issue 2 (20th December 2021) - Meng, Fengxi; Yuan, Yiqun; Ren, Hui; Yue, Han; Xu, Binbin; Qian, Jiang
Abstract: Small ubiquitin‐like modifier (SUMO)ylation is one of the posttranslational modifications and is implicated in many tumor types. Modulation of SUMOylation can affect tumor progression, but the underlying mechanisms remain unclear. Here, we show that, for the first time, in uveal melanoma (UM), the most common intraocular malignancy in adults, global SUMOylation is upregulated and participates in tumor growth. Inhibition of SUMOylation in UM is sufficient to reduce tumor growth both in vitro and in vivo. Furthermore, we found that retinoblastoma protein (Rb) is a target protein and a critical downstream effector of the upregulated SUMOylation activity in UM. Increased SUMOylation of the Rb protein leads to its hyperphosphorylation and inactivation in UM cells, promoting UM cell proliferation. In summary, our results provide novel insight into the mechanism underlying SUMOylation‐regulated tumor growth in UM. Abstract : Modulation of small ubiquitin‐like modifier (SUMO)ylation can affect tumor progression, but the underlying mechanisms remain largely enigmatic. Here, we report that SUMOylation is significantly upregulated in uveal melanoma (UM) and promotes tumor growth. Mechanically, we report that retinoblastoma protein is a target protein and the critical downstream effector of the upregulated SUMOylation in UM.